THE USE OF HANGMAN GAME IN MOTIVATING STUDENTS IN LEARNING ENGLISH - Manan, Rika Mandasari (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2016)
Abstract In learning foreign language such as English, a learner should have motivation in order to have willingness to learn. This study is an attempt to investigate the studentsâ motivation in learning English by using Hangman Game. And this study was to find out if the use of Hangman game motivates the students in learning English. The method used in this study was quantitative with experimental research design. The target population of this study was the eighth grade students of MTs Negeri Cirebon 1. The writer took two classes as samples and the number of the samples was 36 students. The samples were divided into experimental group and control group. There are two research instruments which were used to collect data. They were questionnaire and observation. The result analysis of observation showed that the students in experimental group had higher motivation than in control group. Meanwhile, the calculation of the value of the questionnaire showed that there were significant differences between experimental group and control group. The result of taccount was 2,44 while the result of ttable was 1,994. It was mean that the value of taccount (2,44) > ttable (1,994). So, hypotheses alternative (Ha) was accepted or the use of Hangman game motivate the students in learning English to eighth grade students of MTs Negeri Cirebon 1. Keywords: Hangman Game, Motivation, Learning, English